Daily Stressors Questionnaire for Adolescents - L.A. Golovey; O.S. Galasheva (Психолого-педагогические исследования, 2024)
The article presents the results of the development and testing of psychodiagnostic tools designed to study adolescents’ perception of everyday stress. Everyday stress is an integral part of life in the modern world, and teenagers can be especially vulnerable to everyday stressors. Despite a growing body of research, there is a lack of necessary tools to identify stressful areas in adolescents' daily lives. The article presents research materials obtained from a sample of 555 adolescents, 339 girls and 216 boys aged 13 to 17 years. Validization included a preliminary survey of adolescents, compiling a list of stressors in the everyday life of adolescents, factoring stressors and identifying zones of stress intensity, interpreting the data obtained, assessing zones of everyday stress and convergent validity. As a result, a questionnaire on daily stress for adolescents was developed and tested; zones of everyday stress were identified, including both spheres of the external environment and internal life: “Loneliness, health”, “Self-attitude”, “Rejection”, “Fears, anxieties”, “School, study”, “Communication with elders”, “Affairs, planning”, “Finance”, “Mystical fears”. The results of the analysis showed high consistency of the Questionnaire factors.